Pemanfaatan Game Power Point untuk Stimulasi Kognitif Anak Usia Dini - Purnamasari, Yayu Mega; Ratnadina, Nika (PG PAUD Universitas Negeri Surabaya, 2023)
Cognitive is one aspect of development in children that needs to be properly stimulated in order to develop optimally. Games can be used as an alternative in stimulating aspects of cognitive development, where games contain various materials and problem solving which are part of cognitive development. This study aims to produce power point games to stimulate cognitive abilities in children aged 4-5 years with the theme of transportation. The characteristics of this game are fun, motivating and entertaining. This research is a development research using the ADDIE approach which consists of analyze, design, develop, implement, evaluate stages. then the results of the study used a descriptive approach. Before being tested, the product was validated by media and material experts using a validation sheet. Furthermore, the product was tested using observation data collection techniques, documentation and children's responses, and analyzed and described. The test subjects in this study were children aged 4-5 years. The results of expert validation show that the product is feasible to be tested with a percentage value of 83.7%. The observation results show that children can complete the game well on the material of composing words, mentioning parts, and being able to distinguish land, sea and air transportation with the help of a companion. From the results of this study, it can be concluded that powerpoint-based games are feasible to use and can stimulate cognitive early childhood. Nevertheless, this research requires further and broader study.